Biomarkers of presbycusis and tinnitus in a Portuguese older population - Haider, Haula F.; Flook, Marisa; Aparicio, Mariana; Ribeiro, Diogo; Antunes, Marilia; Szczepek, Agnieszka J.; Hoare, Derek J.; Fialho, Graca; Paco, Joao; Caria, Helena (Frontiers Media, 2017)
Introduction: Presbycusis or age-related hearing loss (ARHL) is a ubiquitous health problem. It is estimated that it will affect up to 1.5 billion people by 2025. In addition, tinnitus occurs in a large majority of cases with presbycusis. Glutamate metabotropic receptor 7 (GRM7) and N-acetyltransferase 2 (NAT2) are some of the genetic markers for presbycusis.